Convergent and predictive validity of vignettes as alternative measure of selfregulation in early adolescence - Brković, Irma (Array, 2011)
useful framework for research of development in adolescence. In this period goal management strategies develop and form the basis for goal-oriented behaviours later in life. The questionnaire for assessing selection, optimization and compensation, especially its dichotomous form, although applicable in adolescence, was found to have several shortcomings. In younger groups the scales reached low reliability and some of its content was too abstract to be validly answered in self- report form. Within Zagreb Personality and Parenting Longitudinal study, we developed 10 pairs of vignettes as an alternative measure of self-regulation. Each pair contains two age-adjusted stories that describe the same situation, but different reaction of the actor, indicative or counter- indicative of usage of the self-regulatory process assessed. We applied vignettes to a total of 861 children aged 10 to 15 years, of whom 338 were followed over a 2-year period and assessed three times, with 1-year interval between assessment points. In addition to vignettes, children also filled in shortened form of the original SOC-questionnaire, containing 24 dichotomous items. Results indicate that vignettes reach good reliability and good convergence with selection and optimization/ compensation questionnaire scales. Vignettes also show expected patterns of correlations with parenting. Although vignettes were found to be good alternative for SOC-measures, their contents has only limited applicability to older adolescents. Advantages and disadvantages of both types of measures for assessing self regulation in early adolescence are discussed.